GAYA PENULISAN PUISI PENGARANG KALIMANTAN BARAT - NFN Musfeptial (tuahtalino, 2018)
This research is entitled Writing Style of Poetry of the Author of West Kalimantan. This study uses descriptive analysis approach. Meanwhile, the theory used in this study is semiotic theory. The results of the study show that there are semiotic differences in the style of poetry writing by three West Kalimantan writers. Each writer represents their respective times. In creating poetry works they have their own characteristics which are depicted in their poetry work. Munawar Kalahan's style of writing is based on his life in his hometown. Meanwhile, Yudhiswara poetry expresses criticism of social phenomena that exist in society. While Ibnu Hs authorship style is more abstract.